Nāṭyaśilpī Buddhadeba Basu - Ghosha, Jagannātha (Śiśirakumāra Bhāduṛi Inasṭiṭiuṭa apha Ḍrāmāṭika Risārca eṇḍa Kālacāra, 1978)
On the dramatic genius of the Bengali litterateur Buddhadeva Bose, 1908-1974.